(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The Sultanate of Oman boasts a flourishing marine sector because of its advantageous geographic location. A successful exploitation strategy will benefit the economy. Appropriate policies must be put in place within certain timeframes in order to activate the function of B.E. activities and ensure their contribution to economic stability and variety. The research examined the evolution of the Omani economy’s B.E. parameters from 1990 to 2022 using a descriptive analytic technique. The most significant of the research’s findings, in terms of fishery indicators, is that artisanal fishing contributes more than other forms of fishing, followed by commercial and coastal fishing, while aquaculture accounted for the smallest percentage during the study period. In terms of licenses, the average number of licenses grew throughout the course of the study, indicating the growing significance of B.E. operations in the Omani economy. Because of the Sultanate of Oman’s unique geographic position, sea transportation contributes significantly to transportation indicators, followed by land and air transportation. The increasing significance of sea transport as a B.E. industry is further supported by this.